CRIMINALIZATION OF DEEPFAKE PORNOGRAPHY OFFENSES: THE URGENCY OF REGULATION UNDER THE ELECTRONIC INFORMATION AND TRANSACTIONS LAW - Novalinda Nadya Putri; Muhammad Enaldo Hasbaj (CV. RADJA PUBLIKA, 2025)
Deepfake pornography enables the manipulation of an individual’s image or likeness into explicit content without consent, resulting in severe harm to personal dignity, privacy, reputation, and psychological well-being. This study aims to examine the urgency of criminalizing deepfake pornography within Indonesia’s legal framework, particularly under the Law on Electronic Information and Transactions (UU ITE), which currently lacks explicit regulation addressing this phenomenon. Employing a normative juridical research method, this study analyzes relevant Indonesian legislation, including the UU ITE, the Pornography Law, and the Criminal Code, alongside fundamental principles of criminal law. A comparative legal approach is also adopted by examining regulatory responses in several jurisdictions, such as the United States, the European Union, and Japan, which have implemented more specific and adaptive legal measures against deepfake-related offenses. The findings reveal significant legal gaps in Indonesian law that hinder effective law enforcement and fail to provide adequate legal protection for victims. Consequently, this study argues that the explicit criminalization of deepfake pornography within the UU ITE is essential to ensure legal certainty, enhance victim protection, and strengthen cybercrime enforcement mechanisms. The study further recommends regulatory reform that integrates criminal sanctions, platform accountability, and victim-oriented remedies as part of a comprehensive legal response to technology-driven sexual exploitation in the digital era.